Is Co-working Increase Survivability? Study on how Collaborating and Networking Facilitates Open Innovation Process for Startups - Elissa Dwi Lestari (Universitas Multimedia Nusantara, 2020)
Startups, as they are bounded to their liabilities of newness and smallness, need to collaborate extensively with their external partners through the open innovation process. This study aims to depict Co-working space's pivotal role in building up a working innovation ecosystem that facilitates open innovation for startups. To get a more deep understanding of the phenomena, this study used an exploratory study based on three case studies of Co-working spaces operated in the Jakarta region. The study shows that the open innovation process among startups is not naturally existed, but instead, it is purposefully designed by the role of a community manager who acts as the ecosystem catalyst. The community manager becomes the ecosystem enablers that facilitate the networking process by connecting members. As a result, these activities will help the emerging of mutual connection and collaboration processes among members that empower open innovation among startups members. The multiple-case design makes the study conclusions might be difficult to generalize. Future research, including quantitative studies, will help the conclusions examination and the knowledge enrichment of start-ups' open innovation process. This paper will enrich the knowledge concerning how Co-working spaces member seizing opportunities that lead to the open innovation process.